2018
DOI: 10.1186/s13578-018-0222-6
|View full text |Cite
|
Sign up to set email alerts
|

Syncytium calcium signaling and macrophage function in the heart

Abstract: Macrophages are traditionally viewed as a key component of the immunity defense system. Recent studies have identified resident macrophages in multiple organs including the heart, in which the cells perform their crucial role on tissue repair after myocardial infarction (MI). The cardiac-specific macrophages interdigitate with cardiomyocytes particularly at the atrioventricular node region. The integrative communication between macrophage and cardiomyocytes can modulate the contractile function of the heart. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…One recent study suggested that TRPV2, as well as the TRP superfamily M2 (TRPM2) may be involved in this myocyte-macrophage interaction at the intercalated disk, by a mechanism that is yet to be investigated. It is postulated that this chain of events enables the formation of a connecting structure between macrophages and cardiomyocytes, along with the extracellular matrix, which guarantees synchronization of cardiomyocyte contraction (78).…”
Section: Trpv2-expressing Resident Cardiac Macrophagesmentioning
confidence: 99%
“…One recent study suggested that TRPV2, as well as the TRP superfamily M2 (TRPM2) may be involved in this myocyte-macrophage interaction at the intercalated disk, by a mechanism that is yet to be investigated. It is postulated that this chain of events enables the formation of a connecting structure between macrophages and cardiomyocytes, along with the extracellular matrix, which guarantees synchronization of cardiomyocyte contraction (78).…”
Section: Trpv2-expressing Resident Cardiac Macrophagesmentioning
confidence: 99%
“…In both tumorigenesis and cardiovascular pathology, calcium (Ca 2+ ) is considerate to be an essential constituent vital to the healthy physiology and disease pathology of both tumor cells and myocytes [21][22][23][24]. In regulation of cellular proliferation and apoptotic death, AKT/ AMPK pathway control the cell cycle by targeting on critical point of G2/S transition functioning along with Ras and Cyclin D1.…”
Section: Introductionmentioning
confidence: 99%
“…As the most complicated issue, physiological function and disorder of heart are determined by multiple factors including EC coupling pathway in cardiomyocytes [82], voltage-dependent gate and connexins pathway in cardiac conduction system [83], macrophage associated regulation of cardiac conduction [82,84], and nutrient delivery involved epithelial vascular system. It is rational to believe that the molecular mechanism of long-term MICT exercise on improvement and protection of cardiac function should be involved in the most pathways related to daily cardiac physiology.…”
Section: Classification Of Long-term Exercise Models and Exercise-indmentioning
confidence: 99%